Morpho-physiological and anatomical characteristics of Urochloa brizantha cv. Marandu in silvopastoral and monoculture systems - Sousa, Luciano Fernandes; Moreira, Guilherme Rocha; Lemos Filho, José Pires de; Paciullo, Domingos Savio Campos; Vendramini, João Maurício Bueno; Luna, Robert Emilio Mora; Maurício, Rogério Martins (Acta Scientiarum. Animal Sciences, 2023)
To gain insights into the forage morphological and anatomical characteristics in a silvopastoral system (SPS) with Bolsa de Pastor (Zeyheria tuberculosa) and palisadegrass ‘Marandu’ (Urochloa brizantha) monoculture (MONO). The SPS was established through natural regeneration of the tree species. Treatments were a SPS and MONO distributed in a completely randomized design with six replicates and repeated measures were the harvest periods. Response variables were morpho-physiological and anatomical characteristicss: green: dead material ratio, leaf blade: stem+sheath ratio, leaf area index, chlorophyll and carotenoid concentrations, proportions of non-lignified and achlorophyllous areas, lignified areas in stems, proportions of non-lignified and achlorophyllous areas, lignified and chlorophyllous areas in leaves, as well as cell length in longitudinal section of stem. Morpho-physiological patterns were altered (p < 0.05) under natural shading conditions due to higher photosynthetic efficiency in the SPS. There was no effect (p > 0.05) of the systems on anatomical patterns, proportions of non-lignified and achlorophyllous, lignified and chlorophyllous tissues, these proportions were influenced only by the periods of the year, both for stems and leaves. Cells of the internodes of the grasses of the studied systems had the same length. The SPS alters morpho-physiological characteristics of palisadegrass and increases the concentration of chlorophyll a and b.